(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study aims to analyze the focalization techniques applied in Tima Shomali’s film AlRawaby School For Girls Season 2, with reference to the narratological theoretical framework developed by Gérard Genette. The main focus of the study lies on three types of focalization: zero focalization, internal focalization, and external focalization with types of bullying, namely physical, verbal, social, and cyberbullying. Using a qualitative-descriptive method, this study identifies and analyzes how the three types of focalization are used to convey the narrative, shape the audience’s perception, and construct social meaning in the storyline. The results show that the film is dominated by internal focus centered on the characters who are victims of bullying, thus presenting a subjective and empathetic narrative. In addition, there is also a shift to external focalization in several scenes that show the objective reality of bullying as a social phenomenon. In other words, the film AlRawaby School For Girls Season 2 not only depicts the personal experiences of the victims, but also highlights the structural and systemic aspects of bullying in a broader social context.